Pragmatism Matters: The Moderation Effect of Pragmatism on the Path between Commitment HRM Practices to Doctor-Patient Relationships and Turnover Intention - Ma, S.; Xu, X; Trigo, V.; Ramalho, N. (The Ninth International Symposium on Multinational Business Management-- Entrepreneurship, Organizational Change and Employment Management, 2017)
This study intends to test whether commitment HR practices followed by hospitals translate into better doctor-patient relationships (DPR) and lower turnover intention, taking into consideration their high vs low sense of pragmatism. With a full sample of 508 clinicians we measured the degree of pragmatism (297 low, 211 high) and conducted a moderated SEM analysis. Findings show that pragmatism has a significant moderation effect in the paths established from commitment HR practices to DPR and turnover intention in such a way that, in the low-pragmatism sample, commitment HR practices associate with better DPR while DPR associates with lower turnover intention. Conversely in the high pragmatism sample commitment HR practices associate with better DPR, but DPR does not associate with lower turnover intention. Overall, commitment HR practices are effective in improving DPR for all clinicians surveyed but its effectiveness on turnover intention is contingent upon the pragmatism-level of the respondents.